Disease Diagnosing Using Bipolar Pythagorean Fuzzy Matrix - K. Lalitha; V. Sivasankari; M. Kavitha (Utilitas Mathematica, 2025)
In this paper, we use composition operator to diagnose disease which results appropriate examination for bipolar Pythagorean fuzzy matrix. It consists of both negative, positive membership and non-membership.